Efektivitas Pengelolaan Dana Bantuan Sosial Kepada Masyarakat Eks Penyandang Kusta Pada Dinas Sosial Provinsi Sulawesi Selatan - Al, Andi Haerul Abdu; Suhendra, Suhendra; Hasma, Hasma (Universitas Patria Artha, 2025)
This study aims to analyze the effectiveness of social assistance fund management for former leprosy patients at the South Sulawesi Provincial Social Affairs Office in 2025. The research method used is qualitative, with primary data collected through interviews and secondary data from Social Affairs Office documents. Data analysis was conducted descriptively to determine the extent to which social assistance funds were distributed appropriately, in accordance with regulations, and had a positive impact on recipients. The results of the study indicate that the management of social assistance funds is not yet fully effective, particularly in terms of planning and implementation, which still face technical, administrative, and social challenges. The planning stage is deemed ineffective due to insufficient quarterly assistance fund allocations and inaccurate data collection. The implementation stage is also ineffective due to complex verification processes, delays in distribution, and social stigma toward recipients. Reporting is considered effective with regular reporting and external oversight, though delays and reliance on manual processes persist. The accountability phase is considered effective, with transparency and accountability maintained through comprehensive reporting and regular audits. In conclusion, comprehensive improvements are needed to ensure that social assistance fund management achieves its objectives in an optimal and fair manner.